Towards a contingent model of key staff retention: The new psychological contract reconsidered - Gregory Lee (South African Journal of Business Management, 2001)
Theories and evidence of widespread changes in employment relationships abound in literature. The organisational environment is increasingly characterised by mandates of flexibility, reorganisation, reengineering and downsizing. As a result, traditional perceptions of what is owed between an employee and an organisation are subject to reappraisal. Such perceptions are encapsulated by the concept of the `psychological contract'. Evidence suggests that in the transient global business environment, the psychological contract of employees and organisational representatives may be shifting towards a far more transactional paradigm. Transactional contracts describe perceptions that employment obligations are more short-term, work content based and less relational. However in the case of key employee groups, such transactional relationships may conflict with an organisation's need to retain its core skills and knowledge that form one of its only truly sustainable competitive advantages. Therefore divergent and varied psychological contracts increase the difficulty of decisions regarding the long-term retention of key employees. An explanatory model is therefore presented here, allowing for the various permutations and effects on key staff retention that may arise from such differing perceptions. Organisational solutions and research propositions are suggested for future research.
Keywords: 650